EZH2 as a novel therapeutic target for atrial fibrosis and atrial fibrillation. (October 2019) - Song, Shuai; Zhang, Rui; Mo, Binfeng; Chen, Long; Liu, Liang; Yu, Yi; Cao, Wei; Fang, Guojian; Wan, Yi; Gu, Yue; Wang, Yuepeng; Li, Yigang; et al.
Abstract: Angiotensin II (Ang-II)-induced fibroblast differentiation plays an important role in the development of atrial fibrosis and atrial fibrillation (AF). Here, we show that the expression of the histone methyltransferase enhancer of zeste homolog 2 (EZH2) is increased in atrial muscle and atrial fibroblasts in patients with AF, accompanied by significant atrial fibrosis and atrial fibroblast differentiation. In addition, EZH2 is induced in murine models of atrial fibrosis. Furthermore, either pharmacological GSK126 inhibition or molecular silencing of EZH2 can inhibit the differentiation of atrial fibroblasts and the ability to produce ECM induced by Ang-II. Simultaneously, inhibition of EZH2 can block the Ang-II-induced migration of atrial fibroblasts. We found that EZH2 promotes fibroblast differentiation mainly through the Smad signaling pathway and can form a transcription complex with Smad2 to bind to the promoter region of the ACTA2 gene. Finally, our in vivo experiments demonstrated that the EZH2 inhibitor GSK126 significantly inhibited Ang-II-induced atrial enlargement and fibrosis and reduced AF vulnerability. Our results demonstrate that targeting EZH2 or EZH2-regulated genes might present therapeutic potential in AF. Highlights: EZH2 expression was significantly elevated in atrial muscle specimens of patients with atrial fibrillation. EZH2 regulates the transformation and migration of atrial fibroblasts. EZH2 regulates fibroblasts transformation mainly through Ang-II-TGF-β-Smads signaling pathway. EZH2 inhibitor GSK126 significantly inhibits Ang-II-induced atrial enlargement, fibrosis, and reduced AF vulnerability.